2010
DOI: 10.1016/j.jpainsymman.2009.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Beliefs and Attitudes About End-of-Life Care: A Comparison of Selected Regions in Hungary and the United States

Abstract: These results illustrate some of the important differences in physicians' beliefs about the care of terminally ill patients between the two countries and can be used to guide medical education and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…31 possibly indicating that out-of-hospital end-of-life care services are not optimal, which might be due to the more recent development of these services in these countries. 33,34 These differences in place of death might suggest that the most appropriate setting as place of death might not be the same in each country (ie, that a hospital setting might prove to be best in one country and a home setting in another), possibly reflecting organizational differences in end-of-life care provision. Furthermore, as one recent study shows that cross-country variation in health-behaviors might be explained by differences in cultural values, perhaps this might partially explain why older people with dementia in neighboring countries, such as Belgium and the Netherlands, have a different likelihood of dying in hospital.…”
Section: Discussionmentioning
confidence: 99%
“…31 possibly indicating that out-of-hospital end-of-life care services are not optimal, which might be due to the more recent development of these services in these countries. 33,34 These differences in place of death might suggest that the most appropriate setting as place of death might not be the same in each country (ie, that a hospital setting might prove to be best in one country and a home setting in another), possibly reflecting organizational differences in end-of-life care provision. Furthermore, as one recent study shows that cross-country variation in health-behaviors might be explained by differences in cultural values, perhaps this might partially explain why older people with dementia in neighboring countries, such as Belgium and the Netherlands, have a different likelihood of dying in hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Csikos et al (2010) compared the attitude of Hungarian and American physicians about hospice cares and reported that both American and Hungarian physicians have a positive attitude towards providing these services. In addition, positive attitude of nurses in this study is consistent with the results of other similar studies (Cramer et al, 2003;Stephan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The data collection was conducted by using a questionnaire designed based on an extensive literature review (Cramer et al, 2003;Stephan et al, 2008;Csikos et al, 2010). This questionnaire was consisted of three main parts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCCS program was originally a bottom-up initiative that addressed the need for on-site palliative care and better management of patient pathways. The programme was introduced by a recognized specialist in palliative care in Hungary, who gained experience in the United Kingdom and the United States and transferred knowledge from abroad [20]. The PCCS sought to match its service portfolio to the needs defined by the clinical departments.…”
Section: Discussionmentioning
confidence: 99%